INFORMATION TECHNOLOGIES IN OPTIMIZING SCIENTIFIC RESEARCH IN THE SPHERE OF THEORETICAL AND APPLIED LINGUISTICS IN THE DIGITAL AGE - M. V. Kamensky (Гуманитарные и юридические исследования)
The article contains the results of analysis of viable trajectories of optimizing the linguistic scientific workflow using contemporary applied linguistics methodology, corpus analysis methods and natural language processing techniques. The author provides practical recommendations for choosing and using modern free and open source linguistic software in various theoretical and applied linguistic studies. An extended classification of linguistic software is provided, on the basis of functionality, cross-platform compatibility, free licensing, and open source model of release. Recommendations are given for the best practices of integrating the corpus management, lexicographic, machine and computer-aided translation, and phonetic software, as well as programming languages with support for natural language processing algorithms, into the linguistic scientific workflow. General purpose software which can be used as an optimizing factor in the linguist’s workflow is also discussed. The article is topical due to the active processes of integrating digital technologies in science in the recent years, introduction of applied methods of research in the context of studies in the theory of language, and the imminent merge of theoretical and applied linguistics in a single scientific specialty according to the classification of the Russian Higher Attestation commission. The scientific novelty of the research is seen in the complex and systematic approach to the problem of analysis of the linguistic scientific workflow in the context of free and open source software which does not require commercial licensing. Another innovative element of the research is the extended definition of the term “linguistic software”, which includes not only the software meant strictly for solving problems in the sphere of studying languages and speech, but also general purpose software that can serve as an aid in preparing and editing reports containing the results of linguistic scientific research.